Pengaruh Leverage, Profitabilitas Dan Ukuran Perusahaan Terhadap Kinerja Keuangan Dengan Good Corporate Governance Sebagai Variabel Moderasi - Aditya, Delista; Ayi Jamaludin Aziz; Maria Magdalena Melani (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2025)
This study aims to examine the effect of leverage, profitability, and company size on financial performance. The object of this study is food and beverage companies in 2019-2023. Leverage is measured by Debt to Equity Ratio (DER), Profitability is easured by Net Profit Margin (NPM), Size is measured by total assets, Financial Perfomance is measured by Return on Equity (ROE) and Good Corporate Governance mechanism proxied by Management Ownership. This type of research is quantitative research. This sampel used in this study was obtained uing the purposive sampling method based on previously determined criteria, namely from food and beverages companies. The method used in this study is multiple linear analysis and moderated regression analysis (MRA) using the Eviews program 12. The results of the study indicate that leverage and profitability has an effect on financial performance, Size has no effect on financial performance, good corporate governance is able to moderated the effect of leverage and profitability on financial perfomance (Weakening) and good corporate governance is able to moderated the effect of size on financial perfomances (strengthening).